THIN CAPITALISATION RULE: INTERSECTION POINT OF TAX DISPUTE SETTLEMENT INSTITUTIONS CASE-LAW AND THEORETICAL ANALYSIS - Endrijaitis, Martynas (Teisė, 2017)
The article discloses the meaning, conceptions, trends of thin capitalisation rule and tax dispute settlement institutions case-law explanations about thin capitalisation rule application. Analysis is performed to discuss problems of relationships between tax dispute settlement institutions case-law and theoretical analysis of thin capitalisation rule.